Description of Parenting Styles of Parents with Autistic Children and Their Accompaniment Treatment - Belaweni, Boy Marjes; Junias, Marylin Susanti (Journal of Health and Behavioral Science, 2025)
Abstract. This study aims to describe the parenting styles of parents and the treatments provided to children with autism. The research employed a descriptive quantitative method with purposive sampling, involving 20 parents of children with autism aged 3–6 years at the Autism Service Center in Kupang. The instrument used was the PSDQ-Short Version questionnaire, which has been tested for validity (r > 0.422) and reliability (α = 0.912). The results showed that the democratic parenting style was the most widely applied, especially by parents aged 30–54 years with high school and undergraduate education. Meanwhile, a combination of democratic and permissive parenting was found among parents aged 55 years with a postgraduate education. Speech therapy and behavioral therapy were the most frequently used (90.23%), while sensory therapy was less applied (72.18%). Keywords: Autistic Children, Parenting Styles, Treatment